MPV17-related hepatocerebral mitochondrial DNA depletion syndrome (MPV17-NNH) revisited - Qualls, Clifford (eNeurologicalSci, 2016)
MPV17-related hepatocerebral mitochondrial DNA depletion syndrome (previously known as Navajo neurohepatopathy) was discovered in children in the Four Corner's region of New Mexico approximately 40 years ago. This disease is associated with a single missense mutation in exon 2 in the MPV17 gene. The syndrome has now been recognized world-wide. We find that huge quantities of neurotoxins were present in archived nervous tissues from such patients. Arsenic was increased 18 ×, cadmium ~ 10 ×, cobalt 2.5 × and manganese 2.3 ×; the largest increase was in mercury content 16,000 × compared to contemporaneous fresh-frozen normal nervous tissues. In the Four Corner's region of NM the life span is reduced compared to other parts of the United States and in our patients with MPV17-NNH the average life span was 5.4 years ± 2.7 (SE) years. We now live in the Anthropocene an epoch characterized by large additions to the biosphere of neurotoxins. The effects of such toxic loads on human health and disease remain to be assessed. We speculate how such high neurotoxin content in tissues, which is likely to increase during the Anthropocene, may have influenced MPV17-NNH and similar phenotypes in different parts of the world. Our results imply that selenium supplementation to the diet in the Four Corner's region of NM might be beneficial to normal people and in the management of patients with MPV17-NNH syndrome.